Market Liquidity and Stock Return in the Nigerian Stock Exchange Market - Ibrahim Bello Abdullahi; Segun Kamorudeen Fakunmoju (Bina Nusantara University, 2019)
This research examined the effect of market liquidity, inflation, and exchange rates on stock return in Nigerian Stock Exchange market. The researchers used ex-post facto design and employed secondary data subjected to Auto-regressive Distributive Lag (ARDL) bound test method of analysis within the period of twenty-one years. Findings reveal that in the short run, stock turnover, trading volume, exchange, and inflation rates have affected stock return positively and significantly. In the long run, market turnover has a positive effect. However, inflation and exchange rates have affected stock return negatively and significantly. Then, trading volume has a negative but insignificant effect on stock return, which is all at 5% level of significance. The researchers conclude that market liquidity, exchange, and inflation rates affect stock return. Therefore, the researchers recommend demutualization and transparent structures and adaptive method stabilization in exchange rate policies to increase stock market patronage, minimize transaction costs, and mitigate the market uncertainties.